2019
DOI: 10.1093/sleep/zsz274
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in obstructive sleep apnea phenotypes, the multi-ethnic study of atherosclerosis

Abstract: Study Objectives The bases for sex disparities in obstructive sleep apnea (OSA), is poorly understood. We quantified the influences of event definitions, sleep-state, and body position on apnea–hypopnea indices (AHIs) in men and women, and evaluated sex differences in pathophysiological endotypes. Methods Polysomnography (PSG) data were analyzed from 2057 participants from the multi-ethnic study of atherosclerosis. Alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 32 publications
1
59
3
Order By: Relevance
“…While the mean BMI in our subjects was higher than 31 in both genders, other populations had a mean BMI lower than 30. 19 , 22 , 38 , 39 Putting all these factors together, the group of patients described in this study were from a high-altitude city, in a developing country, and they were older and more obese than those in most of the previous reports.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While the mean BMI in our subjects was higher than 31 in both genders, other populations had a mean BMI lower than 30. 19 , 22 , 38 , 39 Putting all these factors together, the group of patients described in this study were from a high-altitude city, in a developing country, and they were older and more obese than those in most of the previous reports.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies evidenced that OSA patients present different profiles, based on their symptoms, clinical characteristics, and disease severity, nevertheless those articles analyzed populations that differ in many ways such as age, symptoms, sociodemographic, and clinical characteristics. 22–27 However, none of those articles reported clusters from patients exposed to high altitude, which may represent an important modifying factor of OSA phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard of AHI detection is measured by overnight polysomnography in the sleep laboratory, and values of 5–15, 15–30, and >30 are defined as mild, moderate, and severe OSA, respectively ( 54 ). Further, polysomnography could give mechanistic indices such as loop gain, arousal threshold, and pharyngeal collapsibility with validated methods, and it was able to distinguish sex differences in patients with OSA ( 55 ). However, cost and accessibility limit the application of polysomnography in all settings.…”
Section: Update On Diagnosismentioning
confidence: 99%
“…Phenotyping, incidentally, had been previously presented as a promising yet time consuming, techniquesensitive, costly procedure. A recent study has shown that PSG signals can now be used for phenotyping in a retrospective and relatively inexpensive way 8 , thus making the technique more accessible both clinically and financially.…”
Section: Lowering Of the Cost Of Oral Appliance Therapy For The Patientmentioning
confidence: 99%